2022
DOI: 10.1002/smll.202203045
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Conductive and Highly‐Stable Interface for Alkali Metal Anodes

Abstract: Alkali metals are regarded as the most promising candidates for advanced anode for the next‐generation batteries due to their high specific capacity, low electrochemical potential, and lightweight. However, critical problems of the alkali metal anodes, especially dendrite formation and interface stabilization, remain challenging to overcome. The solid electrolyte interphase (SEI) is a key factor affecting Li and Na deposition behavior and electrochemical performances. Herein, a facile and universal approach is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…[1][2][3][4] However, the development of lithium metal batteries (LMBs) has been seriously hindered by dendrite-related safety issues, deriving from an inhomogeneous solid electrolyte interphase (SEI) formed on the surface of the LMA. 5 Various strategies, such as developing highly concentrated electrolytes, 6 or locally concentrated electrolytes, 7 exploring advanced fluorinated ether solvents, 8 synthesizing fluorinated or nitrite salts, 9,10 using dual-or multi-additives, 11 fabricating artificial SEI layers [12][13][14][15][16] and so on, have been proposed to improve the batteries' performance and explore the relationship between the SEI properties and electrochemical performance of the LMA. The consensus is that an inorganic-rich SEI displays a low electroconductivity but a suitable Li + ionic conductivity, enabling efficient de-solvation and uniform Li + diffusion through the SEI layer.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] However, the development of lithium metal batteries (LMBs) has been seriously hindered by dendrite-related safety issues, deriving from an inhomogeneous solid electrolyte interphase (SEI) formed on the surface of the LMA. 5 Various strategies, such as developing highly concentrated electrolytes, 6 or locally concentrated electrolytes, 7 exploring advanced fluorinated ether solvents, 8 synthesizing fluorinated or nitrite salts, 9,10 using dual-or multi-additives, 11 fabricating artificial SEI layers [12][13][14][15][16] and so on, have been proposed to improve the batteries' performance and explore the relationship between the SEI properties and electrochemical performance of the LMA. The consensus is that an inorganic-rich SEI displays a low electroconductivity but a suitable Li + ionic conductivity, enabling efficient de-solvation and uniform Li + diffusion through the SEI layer.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in the literature, the main peak for the Al K edge for Al 2 O 3 at 1564.7 eV is assigned to transitions from the Al 1s orbitals into Al 3p and O 2p antibonding orbitals of t1u symmetry. [ 18 ] In the spectrum for the different compositions, this main peak slightly shifts to the low energy of 1564.4 eV. However, the peaks remain in the same position for the alloy structure (Li@(2ALD‐2MLD)25) and the nano‐laminated structure (Li@(10ALD‐10MLD)5), as shown in Figure S11a (Supporting Information).…”
Section: Resultsmentioning
confidence: 85%
“…Many models have been established to simulate the growth mechanism of lithium dendrites. 91,[103][104][105] Lithium dendrites are a kind of dendrite formed in the off equilibrium state. Various studies have shown that current density and operating temperature have a great influence on the growth of lithium dendrites.…”
Section: Mechanism and Influencing Factors Of Lithium Dendritesmentioning
confidence: 99%